THE INFLUENCE OF PRICE, PROMOTION, AND BRAND IMAGE ON CUSTOMER LOYALTY GOJEK IN CHRISTIAN UNIVERSITY OF INDONESIA, JAKARTA - Diaz , Jhon Chavin; Sembiring, Carolina F. (Universitas Kristen Indonesia, 2021)
The purpose of this study, namely to determine the effect of price, promotion and brand image on customer loyalty Gojek in Christian University of Indonesia, Jakarta. The population in this research are all students in the UKI totaling 5.013 people. The sample used as many as 40 respondents. Sampling was conducted using Non-probability sampling technique with a type of purposive sampling. Data analysis using the technique of multiple linear regression analysis, F test, and t test. The results of the research showed, price and promotion have no influence on customer loyalty partially, as well as the variable brand image has an influence on customer loyalty Gojek in UKI Jakarta. Price, promotion, and brand image simultaneously (together) have an influence on customer loyalty Gojek in UKI Jakarta. Keyword : price, promotion, brand image and customer loyalty